Molecular mechanisms involved in functional macroevolution of plant transcription factors - Romani, Facundo Alihuen (2020)
Transcription factors (TFs) are key components of the transcriptional regulation machinery. In plants, they accompanied the evolution from unicellular aquatic algae to complex flowering plants that dominate the land environment. The adaptations of the body plan and physiological responses required changes in the biological functions of TFs. Some ancestral gene regulatory networks are highly conserved, while others evolved more recently and only exist in particular lineages. The recent emergence of novel model organisms provided the opportunity for comparative studies, producing new insights to infer these evolutionary trajectories. In this review, we comprehensively revisit the recent literature on TFs of nonseed plants and algae, focusing on the molecular mechanisms driving their functional evolution. We discuss the particular contribution of changes in DNA-binding specificity, protein–protein interactions and cis-regulatory elements to gene regulatory networks. Current advances have shown that these evolutionary processes were shaped by changes in TF expression pattern, not through great innovation in TF protein sequences. We propose that the role of TFs associated with environmental and developmental regulation was unevenly conserved during land plant evolution.